The changing organizational basis of African agricultural research - Roseboom, Johannes; Pardey, Philip G.; Beintema, Nienke M. (International Food Policy Research Institute, 1998)
National agricultural research systems in Africa increased markedly in size throughout the past three decades, but from an especially small base. In 1961, public systems in 33 of 48 African countries employed fewer than 25 full-time equivalent (fte) researchers, by 1991 there were only 8 such systems (and 23 countries employed more than 100 fte researchers, compared with only 4 countries in 1961). Despite this overall growth, and the efforts that began in the late 1980s to consolidate the conduct of agricultural research, most African agencies are still very small and fragmented by international standards, making it difficult to realize the scale and scope economies that seem increasingly evident in agricultural R&D conducted elsewhere. This study reports a range of institutional indicators for 341 agricultural research agencies located in 39 African countries. In 1991, 236 agencies (nearly 70 percent of our sample total) employed less than 20 fte researchers. Most public research in Africa is still done by government agencies; they employed 87 percent of the total number of researchers in 1991. University research has grown the most rapidly, but still accounted for only 10 percent of the total number of African researchers in 1991. Partly in response to the small, fragmented, and comparatively isolated structure of agricultural R&D agencies, but partly from local political and, especially, donor pressure too, there has been a proliferation of research networks in recent years. We identified 86 networks, of which 72 involved Africans linked to Africans, a rather parochial strategy in an increasingly interdependent world. Regional approaches to the conduct and funding of agricultural R&D have been revived in more recent years, a feature of much of the regions's research in earlier, colonial times, as we describe here. However, the political and economic realities of today bear little relationship to those of colonial times, and it remains unclear how these regional approaches will prosper and effect meaningful research given the organizational uncertainties that still abound.